Kinetic Aspects of Nitrogen Loss in Presence of Ammonium Persulphate and Mixed Fertilizers in Soils - Dikshit, S.N.; Sharma, K.P.; K. Sharma, Harendra (Asian Journal of Chemistry, 2010)
Indian soils are generally deficient in organic matter and total nitrogen. To meet out nitrogen deficiency nitrogenous fertilizers are added to soils. All added nitrogen is not utilized by the crops and plants. All over the world farmers have observed that the recovery of nitrogen from fertilizers and maneuver in manure crop productions is usually low and of the order of 25-30 %. Nitrogen is lost through various ways such as erosions, leaching, gaseous loss denitrification and chemo denitrification. Soil erosion shows that the quantity of nitrogen removed in runoff water every year varies from 0.13 lb. to 0.53 lb per acre. It is evident that the nitrogen loss follows the first order non-reversible kinetic model in exposed sets (in light). However in covered sets (in dark) there is a departure from linearity. It is evident that the velocity constants are lower for mixed fertilizers than for nitrogen substance alone. The values of velocity constants for mixed fertilizers have been calculated only for the time period up to which the kinetic plots are linear representative. The average values of K × 103 (d-1) are 1.470 (± 0.12) in light and 2.359 (± 0.18) in dark for 0.2 % N + 1 % C + 0.5 % K and 0.25 % P concentrations. The average value of K × 103 (d-1) of 0.2 % concentration of nitrogen is 4.442 (± 0.36).